Microtremor Vibrations in the Soil Experimental Investigation and FEM Simulation - Papanova, Zuzana; Papan, Daniel; Kortis, Jan (Communications - Scientific Letters of the University of Zilina, 2014)
Vibration problems of the building structures caused by technical seismicity are becoming increasingly topical. The aim of this paper is to show FEM simulation of the spreading wave impact, which causes vibration system consisting of subsoil-structure interaction in microtremor. The results of the experiment together with this theoretical analysis and FEM simulation appear to be effective application for engineering experience. They are also used in assessing and predicting the vibration effects induced by technical seismicity due to traffic. [1].
Keywords: FEM simulation; vibration; response; spectrum; soil; interaction